Artificial Intelligence versus Human Intelligence in Team Management: A Comparative Study Based on the Results of a Practical Experiment - BOUFISSIOU, Souad; DJANI, Mourd (Journal of Excellence for Economics and Management Research, 2026)
This study aimed to compare the effectiveness of managing work teams using artificial intelligence (AI) versus traditional human management, based on the analysis of experimental data derived from a practical experiment. The experiment evaluated the performance of design teams tasked with solving a complex engineering problem, where AI systems managed some teams, while human managers managed others. Data on performance, team cohesion, and participant evaluations of the effectiveness of management interventions were analyzed. The results showed that teams managed by AI achieved higher and more consistent performance quality, in addition to higher levels of cohesion compared to teams managed by humans. However, participants reported that they found the interventions of human managers to be more relevant and helpful than those of AI. The study reveals an important trade-off between the efficiency of AI in achieving objective performance and the ability of human managers to provide personalized and adaptive interventions. The findings suggest that a hybrid approach, which combines the strengths of both AI and human management, is the optimal solution for managing contemporary work teams.